Controlling Oxygen Reduction Reaction Activities of Ag@Pt Core–Shell Nanoparticles Via Tuning of Ag in the Surface Layer. Issue 4 (19th February 2023) - Aksoy, Dilan; Karakaya, Cüneyt; Balkan, Timuçin; Savaci, Umut; Turan, Servet; Metin, Önder; Kaya, Sarp
Abstract : Herein, the effect of Pt shell thickness and Ag content in the surface layer on the oxygen reduction reaction activities of Ag@Pt core@shell nanoparticles (NPs) is discussed. Ag@Pt NPs are synthesized via the seeded‐growth method, where colloidal Ag NPs are first synthesized and used as seeds for the growth of Pt. Electrochemical activity measurements in alkaline media show a remarkable dependency between the Ag content in the shell and the oxygen reduction reaction (ORR) activity, where the overpotentials required for −1.0 mA cm −2 drop gradually, that is, 0.72, 0.77, and 0.80  V RHE for Ag@Pt‐25, Ag@Pt‐35, and Ag@Pt‐45, respectively. Tafel analysis also confirms this dependency with 73.5 mV dec −1 for Ag@Pt‐25, 71.3 mV dec −1 for Ag@Pt‐35, and 68.8 mV dec −1 for Ag@Pt‐45. A combination of the high‐resolution transmission electron microscope, X‐ray photoelectron spectroscopy, and X‐Ray diffraction analysis shows an increase of the Pt shell thickness. It is shown that the absence of Pt‐H adsorption/desorption peaks in cyclic voltammetry of Ag@Pt NPs is correlated with Ag in the surface layer, which plays an important role in the ORR activity due to the blockage of Pt(111) terrace sites. Rate‐limiting first‐electron transfer to oxygen is facilitated by decreasing Ag amount at the surface. Abstract : Ag@Pt core–shell nanoparticles are very promising in terms of electrocatalytic activity and durability toward the electrocatalytic oxygen reduction reaction (ORR). Pt layer thickness in Ag@Pt core–shell nanoparticles can be controlled in the synthesis stage; however, the ORR activity is not solely dependent on the Pt overlayer.